Effect of particulate matter (PM 10) pollutant concentration on peak expiratory flow rate score in junior high school students - Niken Sawitri; Oma Rosmajudi; Dedi Subardja; Heda Melinda D N (Paediatrica Indonesiana, 2003)
Background Various pollutants especially particulate matter withdiameter of 10 micrometer or less (PM 10) reduce the function oflung. However, its effect to peak expiratory flow rate (PEFR) as aparameter of central airway resistance is still inconsistent.Objective This study was designed to assess the impact of differ-ent PM 10 concentration to PEFR score among junior high schoolstudents who live in two areas.Methods It was a descriptive analytical study with cross sectionaldesign to junior high school students who lived in areas with highPM 10 i.e, Cililin sub district (252.63 mg/m 3 /h) and low PM 10 i.e.,Paseh sub district (27.15 mg/m 3 /h). PEFR was measured by usingMini Wright Peak Flow Meter and body weight by microtoire. Dataof indoor pollutants were collected from questionnaires.Results There were 463 subjects, 242 students in Cililin and 221students in Paseh, who fulfilled the inclusion criteria which wereaged 12 â€“15 years, living more than one years continuously withinradius of 5 km from the location of pollutant measurement, nonsmokers, and considered â€œhealthâ€ according to history taking andphysical examination. The PEFR score in Cililin (305.9+57.9 l/min)was significantly lower than that in Paseh (327.7+54.8 l/min (t=4.15;p<0.001)).Conclusion Although the influence of indoor pollutants especiallycooking stoves could not be ignored, the difference of PEFR scorein these two groups were possibly due to the different concentra-tion of PM 10